Analisis Aktivitas Investasi dan Pendanaan pada Perusahaan yang Terdaftar di BEI (Pada PT. Hero Supermarket Tbk Tahun 2020-2022) - Mentari Fadila Salem; Iryanti Leuly; Raico Ronald Tebyiary; Wa Ode Widia; Nur Hani Salampessy; Christina Sososutiksn (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Investing activity is the acquisition and disposal of long-term assets and other investments that are not included in cash equivalents. 4. Financing activities are activities that result in changes in the amount and composition of Bank capital and loans. This study aims to present: (1) analysis of investment activities in PT. HERO SUPERMARKET TBK, (2) analysis of funding activities at PT. Hero Supermarket Tbk. The design of this research is quantitative research and data research. The data studied are the national financial reports from the Indonesian stock exchange PT. Hero Supermarket Tbk, the results of the study show that (1) investment activity at PT. Hero Supermarket Tbk, showing good performance so that investment continues to increase every year, (2) financing activities run smoothly and stably despite being disrupted by the Covid-19 outbreak in Indonesia.